1964
DOI: 10.1007/bf02898132
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of monocarbonyls from autoxidizing lipids

Abstract: AbstractsIn an attempt to account for carbonyls found in oxidized lipid systems, but not theoretically predicted from the decomposition of lipid hydroperoxides, a member from each of the monocarbonyl classes commonly observed in oxidizing lipids was oxidized at 45C in a Warburg apparatus and the carbonyl products studied. The carbonyl compounds used weren‐nonanal,n‐non‐2‐enal,n‐hepta‐2,4‐dienal andn‐oct‐1‐en‐3‐one. Nonanal was relatively stable to oxidation and was oxidized to nonanoic acid. Oct‐1‐en‐3‐one did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0
2

Year Published

1965
1965
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(40 citation statements)
references
References 20 publications
3
35
0
2
Order By: Relevance
“…14/15) during refrigerated storage of boiled chicken can be explained on the basis of model experiments performed by Lillard and Day [57] and Schieberle and Grosch [58]. These authors showed that unsaturated aldehydes are more sensitive towards autoxidation compared with the saturated ones.…”
Section: Resultsmentioning
confidence: 95%
“…14/15) during refrigerated storage of boiled chicken can be explained on the basis of model experiments performed by Lillard and Day [57] and Schieberle and Grosch [58]. These authors showed that unsaturated aldehydes are more sensitive towards autoxidation compared with the saturated ones.…”
Section: Resultsmentioning
confidence: 95%
“…For example, from autoxidation of pure 2,4-decadienal at room temperature, a complex mixture of volatile products such as butenal, hexanal, 2-heptenal, 2-octenal, benzaldehyde, glyoxal, trans-2-buten-l,4-dial, furan, ethanol, acrolein, pentane, benzene, and acetic, hexanoic, 2-octenoic and 2,4-decadienoic acids have been identified by Matthews et al (1971). The oxidation of 2-nonenal at 45°C produces C2, C3, C7, C8 alkanals, glyoxal, and a mixture ofC7, C8 and C9 (X-keto aldehydes (Lillard and Day, 1964).…”
mentioning
confidence: 97%
“…34 Por fim, temse a terminação que corresponde à formação de produtos estáveis, produtos secundários de oxidação, obtidos por cisão, e rearranjos dos peróxidos como epóxidos, compostos voláteis e não voláteis. 14,34,35 A Tabela 2 mostra o período em que foi observado o maior índice de peróxido para cada uma das amostras, incluindo o controle. Os tratamentos 3, 5, 6 e 7, os quais continham TBHQ, foram os que apresentaram maior tempo para atingir o índice de peróxido máximo, com destaque para a mistura binária BHT e TBHQ (tratamento 6) que apresentou atividade antioxidante por 16 dias a mais.…”
unclassified